Tetravalent Rabies-Vectored Filovirus and Lassa Fever Vaccine Induces Long-term Immunity in Nonhuman Primates. (9th January 2021) - Kurup, Drishya; Fisher, Christine R; Scher, Gabrielle; Yankowski, Catherine; Testa, AnnaMarie; Keshwara, Rohan; Abreu-Mota, Tiago; Lambert, Rachael; Ferguson, Melissa; Rinaldi, William; Ruiz, Leonard; Wirblich, Christoph; et al.
Abstract: Background: The objective of this study is to evaluate the immunogenicity of adjuvanted monovalent rabies virus (RABV)–based vaccine candidates against Ebola virus (FILORAB1), Sudan virus (FILORAB2), Marburg virus (FILORAB3), Lassa virus (LASSARAB1), and combined trivalent vaccine candidate (FILORAB1–3) and tetravalent vaccine candidate (FILORAB1–3 and LASSARAB) in nonhuman primates. Methods: Twenty-four Macaca fascicularis were randomly assigned into 6 groups of 4 animals. Each group was vaccinated with either a single adjuvanted vaccine, the trivalent vaccine, or the tetravalent vaccine at days 0 and 28. We followed the humoral immune responses for 1 year by antigen-specific enzyme-linked immunosorbent assays and RABV neutralization assays. Results: High titers of filovirus and/or Lassa virus glycoprotein-specific immunoglobulin G were induced in the vaccinated animals. There were no significant differences between immune responses in animals vaccinated with single vaccines vs trivalent or tetravalent vaccines. In addition, all vaccine groups elicited strong rabies neutralizing antibody titers. The antigen-specific immune responses were detectable for 1 year in all groups. Conclusions: In summary, this study shows the longevity of the immune responses up to 365 days for a pentavalent vaccine—against Ebola virus, Sudan virus, Marburg virus, Lassa virus, and RABV—using a safe and effective vaccine platform. Abstract : This study indicates that rabies virus–based vaccines can be blended for multiple antigens from multiple hemorrhagic fever viruses without affecting the immune response compared to single-antigen vaccines. The induced humoral immune responses were long-lived up to the 1-year study time frame.